Communicating without nonprofit organizations on nonprofits' social media: Stakeholders' autonomous networks and three types of organizational ties. (November 2019) - Ihm, Jennifer
Research on nonprofit organizations' (NPOs) social media strategies has focused on the dialogic features of social media to improve organization–stakeholder relationships and elicit stakeholder responses. However, NPOs may initiate different types of relationships with their stakeholders on social media (i.e. flow, representational, and affinity). Stakeholders may also create autonomous networks among themselves beyond simply responding to the NPOs. Based on observations of 100 NPOs' and stakeholders' 1-month-Twitter activities, this study captures varying types of NPOs' ties embedded in social media and examines how each type correlates with stakeholders' autonomous networks. The results suggest that each type of tie has a different role in autonomous networks. This study provides a nuanced understanding of diverse networks embedded in social media and sheds light on autonomous networks as distinctive virtual communities for NPOs during this era of transformation in collective action and social change, existing at the intersection of loose organizational coordination and individual autonomy.